One-step straightforward synthesis of Tb-doped NiO nanocomposites using flash combustion method: Structural, optical, luminescent, and electrical switching properties. Issue 8 (1st June 2020) - Khan, Aslam; Shkir, Mohd.; Ashraf, I.M.; El-Toni, Ahmed Mohamed; Aldalbahi, Ali; AlFaify, S.
Abstract: Herein, we report a novel method for the synthesis of pure and Tb-doped NiO nanocomposites with homogeneity using a non-toxic material, citric acid, via one-step flash combustion at 550 °C. The single cubic phase was determined by X-ray diffraction (XRD) analysis, confirming the high purity of the synthesized products. A systematic reduction and broadening of the XRD peaks was seen with increasing incorporation of Tb, indicating a decreasing particle size from 26 to 7 nm. The zeta potential was approximately −6.7 mV for pure NiO and 19 mV for 20% Tb-doped NiO NPs. The higher value of zeta potential indicates that the doped samples are more stable in aqueous media than undoped samples. FT-Raman spectra revealed the absence of impurity peaks and peak broadening with increasing Tb concentrations. All Raman modes were red shifted in comparison to bulk NiO. EDX/SEM mapping revealed the presence of Tb and its homogeneous distribution within NiO. FE-SEM and TEM confirmed the spherical morphology of NiO when doped with Tb. The surface area and pore volume of 5 wt% Tb-doped NiO NPs was determined to be 18.5 m 2 /g and 8.34 × 10 −2 cm 3 /g, respectively. The energy gap varied with Tb-doping and noticed in the range of 3.5–3.6 eV. An intense single emission peak at 396 ± 5 nm for all Tb-doped NiO NPs was observed. Tb-doped NiO NPs demonstrated ε r ′ values in range of 30–77 at 4 kHz and 20 to 41 at 6 MHz. Dark and photo current-voltage investigations revealed that Tb-doping significantly enhanced the electrical properties of NiO, making them highly applicable for optoelectronic devices.